2010
DOI: 10.1007/s11748-010-0640-9
|View full text |Cite
|
Sign up to set email alerts
|

Short-term and long-term outcomes of octogenarians after off-pump coronary artery bypass surgery

Abstract: Off-pump coronary artery bypass can be performed safely in octogenarians, with excellent early and late outcomes. Careful postoperative follow-up is required to reduce postoperative long-term adverse events. Off-pump coronary artery bypass is a feasible modality of coronary revascularization for octogenarians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…15 Takase et al reported that there was no difference in hospital mortality between octogenarian and younger patients who underwent offpump CABG. 4 Off-pump CABG was performed in 96% of the elderly patients in the present study. The other 4% patients underwent on-pump CABG because of a large heart and severely impaired left ventricular function or intramyocardial coronary arteries.…”
Section: Figmentioning
confidence: 88%
See 1 more Smart Citation
“…15 Takase et al reported that there was no difference in hospital mortality between octogenarian and younger patients who underwent offpump CABG. 4 Off-pump CABG was performed in 96% of the elderly patients in the present study. The other 4% patients underwent on-pump CABG because of a large heart and severely impaired left ventricular function or intramyocardial coronary arteries.…”
Section: Figmentioning
confidence: 88%
“…2 In contrast, recent reports have demonstrated that early postoperative outcomes in elderly patients are improving with the development of devices, surgical techniques, and postoperative management. 1,[3][4][5] The use of arterial grafts is considered to be one of the contributing factors of these improvements. 6,7 However, the selection of grafts for CABG tends to be decided according to the patient's general condition and life expectancy, especially in elderly patients.…”
Section: Introductionmentioning
confidence: 99%
“…As the population ages, the number of octogenarians undergoing cardiac surgery is increasing, as the safety of revascularization procedures for the elderly have made rapid progress, resulting from technical improvements in extracorporeal circulation (ECC) apparatuses, minimally invasive surgical procedures including off-pump coronary artery bypass grafting (OPCAB), and the development of post-surgical management. Numerous reports regarding cardiac surgery for octogenarians have focused on the performance of the surgery itself, graft patency rates, and life expectancy 2 , 3 , 4 , 5 , 6 , 7 ) , and have generally been single-center studies 8 ) . In addition, reports on cardiac rehabilitation in octogenarians after cardiac surgery have mostly focused on the postoperative characteristics of patients with valvular heart disease involving aortic and mitral valves 9 , 10 , 11 , 12 ) .…”
Section: Introductionmentioning
confidence: 99%